National Geographic Magazine [computer file] The 1930s (vol. LVIII, no. 1) Jan. 1930-April 1933, May 1933-August 1936, September 1936-December 1939 (The Complete National Geographic Magazine : 110 years on CD-ROM, 1888)
Rise to record heights in the stratosphere-nearly 14 miles above the earth-in the balloon Explorer II. Plunge half a mile under the sea with William Beebe in his bathysphere. Fly solo to Hawaii with the legendary Amelia Earhart in 1935. Ride along on the first motorized trips through the Himalayas and the first Trans-African motorcycle expedition. And experience many more captivating moments from the 1930s.